Evaluation review of effectiveness and security metrics performance on information technology domain - Roshidi Din; Rosmadi Bakar; Azizan Ismail; Aida Mustapha; Sunariya Utama (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Information Technology (IT) development is the vital required for human life activities in this global era. This implementation of IT system has becomes competitive among developers to increase the quality of system performance. In order to discover the IT performance of system, it neccesary to evaluate the IT implementation performance. It determines the anticipated system output to prepare to enhance the application performance. In this paper the evaluation performance that is reviewd are effectiveness and security metrics because both of evaluations able to improve the development and protection of system. Therefore, this paper classifies some IT domain development that used in term of effectiveness and security metric approach from previous researchers’ effort. It is categorized the domain based on both evaluation term of effectiveness and security metrics from specific parameter their used. The concern of this paper is to discover the important effectiveness and security metrics in IT domain performance that is anticipated to achieve expected performance.